2007
DOI: 10.1021/bi700833h
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Efflux from Macrophage Foam Cells Is Enhanced by Active Phospholipid Transfer Protein through Generation of Two Types of Acceptor Particles

Abstract: Phospholipid transfer protein (PLTP) is expressed by macrophage-derived foam cells in human atherosclerotic lesions, suggesting a regulatory role for PLTP in cellular cholesterol homeostasis. However, the exact role of PLTP in the reverse cholesterol transport pathway is not known. PLTP is present in plasma as two forms, a highly active (HA-PLTP) and a lowly active (LA-PLTP) form. In this study we clarify the role of the two forms of PLTP in cholesterol efflux from [3H]cholesterol oleate-acetyl-LDL-loaded THP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…Notably, ABCG1 mediates cholesterol efflux to mature HDL and, to a lesser extent, to apoB-containing lipoproteins (8). Our data are also in accordance with recent findings that ABCA1-dependent efflux is highly dependent on the availability of preb-HDL (43)(44)(45). These results demonstrate that preb-HDL may be the preferred acceptor for the concerted action of the ABCA1 and ABCG1 pathways, leading to high efflux capacity from THP-1 macrophage to serum with high preb-HDL content.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, ABCG1 mediates cholesterol efflux to mature HDL and, to a lesser extent, to apoB-containing lipoproteins (8). Our data are also in accordance with recent findings that ABCA1-dependent efflux is highly dependent on the availability of preb-HDL (43)(44)(45). These results demonstrate that preb-HDL may be the preferred acceptor for the concerted action of the ABCA1 and ABCG1 pathways, leading to high efflux capacity from THP-1 macrophage to serum with high preb-HDL content.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies (35,47), our low-HDL subjects had smaller HDL mean particle size, a decreased proportion of large HDL particles, and reduced preb-HDL concentration. The effect of HDL particle size on efflux capacity, and the impact of large HDL particles on cholesterol removal were recently demonstrated (45,48,49). As expected, high-HDL subjects demonstrated a higher proportion of large HDL 2b particles.…”
Section: Discussionmentioning
confidence: 58%
“…Finally, results of experimental studies indicated that ANGPTL3 and ANGPTL4 respond differently to fasting and refeeding. In fact, ANGTPL4 is maximally expressed formed pre-HDL particles was quantified by resolving the postincubation plasma samples with two-dimensional crossed immunoelectrophoresis, as previously reported (36). Briefly, the crossed immunoelectrophoresis consisted of an agarose electrophoresis in the first dimension for separation of lipoproteins with their pre, , and  mobility, followed by electrophoresis in the second dimension agarose gel containing 7.5% (v/v) rabbit anti-human apoA-I antiserum.…”
Section: Ofttmentioning
confidence: 99%
“…Such remodeling of HDL particles may depend directly on ABCA1 activity or, more likely, may reflect the activity of macrophage surface or secreted proteins, such as PLTP. 22,23 Therefore it is possible that the increment in cholesterol efflux to HDL seen from both control and ABCG1-silenced HMDM and THP-1 macrophages may reflect ABCA1-dependent export to acceptors generated from HDL.The Cla-1 receptor is robustly expressed in fully differentiated human macrophages (THP-1 and HMDM), and on the basis of the inhibitory effect of a receptor-blocking antibody appears to contribute to the elimination of free cholesterol from cholesterol-loaded human macrophages. This hypothesis is consistent with our observation that depletion in cellular ATP did not alter cholesterol efflux to HDL in the absence of LXR induction, and favors a transport mechanism for which energy is not required.…”
mentioning
confidence: 99%